Nyt syn på Anker Jørgensens økonomiske politik - Asmussen, Balder (Historisk Tidsskrift, 2013)
An Alternative View on Prime Minister Anker Jørgensen's Economic PolicyIn 1973 and again in 1979 the Danish economy was severely affected by soaring oil prices on the international market. Reduced competitive power caused a significant rise in unemployment. This article discusses the response from decision-makers and the effects of policy on the state of the economy. The first course of action in order to handle the challenge of the crisis included a loose fiscal and monetary policy. Meanwhile, competitiveness was slowly restored by way of income policy. Overall results were disappointing, though: further rises in unemployment and balance of payment deficit occurred. Apparently the chosen path led in the wrong direction, but in fact several intentions were realized. More jobs were created – only the size of the workforce rose even faster. The upward trend of wages and salaries was subdued – although not sufficiently, as another price hike in oil aggravated the slump. By necessity, when the second oil crisis set in, the balance of payment problem was given a high priority in order to prevent the loss of discretionary power in national economic policy due to a runaway increase in foreign debt. Competitive power improved as a result of tight income policy combined with repeated devaluations. The result was the first trade surplus since 1958. However, the success was dearly paid. Lower private consumption induced a fall in aggregate demand. The derived unemployment entailed diminished revenues of the State and an internal deficit that kept growing year after year. The judgment of posterity on economic policy in the 1970s has been harsh. Because modern critics are used to having North Sea oil as a source of regular domestic energy supply as well as public revenues, they see the frequent shifts in economic policy in earlier years as a sign of vacillation. In addition, they emphasize the fateful development in macroeconomic key figures, especially unemployment and national and foreign debt. Against this negative assessment, the present article claims that policy shifted in response to changes in real economic conditions. New measures were not a symptom of policy failure or irresolution on the part of the government. Critics have ignored the fact that improved competitiveness was based on decisions from 1979-1981; the effects, however, did not materialize until the upswing of 1983-85. On this background a positive reassessment is in order. In an attempt to state the cause of the prevailing negative appraisal of the economic policy of the 1970s, attention is directed towards current problems and policy debates. In the 1970s Denmark was governed by the Social Democratic Party. Faced with the crisis, Social Democratic leaders sought to hedge in the welfare state and at the same time place a limit on private consumption in order to restore equilibrium. This order of priorities was premised on maintaining social equity even in a period of rough economic measures. By asserting a causal link between on the one side this political attitude and on the other side large internal deficits and the threat of national bankruptcy, centre-right opinion-formers of later years have been counteracting the vision of their social democratic opponents. In other words, negative assessments of economic policy in the 1970s are not only defective per se, they can be interpreted as interventions in a discursive battle about what constitutes an adequate and just redistributive policy. Political controversy aside, the argument of a strong linkage between income distribution policy and general economic policy is still flawed in the historical context of the 1970s. Whether either loose or tight policy were the better choice, and whether one policy instrument were preferable to another, was decided on quite neutral terms. The social profile was indeed important for the Social Democratic government, but at the same time its leaders accepted the advice given by non-partisan experts. Likewise, many of the initiatives condemned and ridiculed by later critics, for instance currency devaluation, were in the epoch supported even by Liberal and Conservative politicians.